The Concept of Minimum Wage for Workers in Law No. 11/2020 in the Perspective of Fiqh Muamalah - Prasetya, Teguh Eka; Nasution, Saipul; Firdaus, Muhammad Irkham; Rasyadi, Muhammad Fakhri (AL- IKTISAB Journal of Islamic Economic Law, 2022)
••• English ••• Law No. 11/2020 on Copyright of Works is a change from Law No. 13/2003 on Employment. The law was passed in 2020. In its ratification, many employees disagreed with some of the articles contained in the law, one of them is Article 89 Paragraph (1) which discusses the minimum wage. Employees do not agree with this article because of the change of the provincial minimum wage to the provincial minimum wage and the district/city minimum wage. It is feared that changes in the minimum wage will create injustice between workers and employers. The purpose of this research is to know and analyze the concept of minimum wage of employees working in Law No. 11/2020 which is guided by fiqh muamalah. The method used in this research is a kind of normative juridical study or literature by taking a statutory and conceptual approach in fiqh muamalah by examining documents through some data to analyze the concept of minimum wage of employees in Law No. 11/2020. The result is that in determining the size of the minimum wage based on employee welfare, Law No. 11/2020 does not correspond to what is described in fiqh muamalah. The researcher suggest that the data used in determining the minimum wage based only on economic growth and inflation must be conditional. Because basically, not all employees can meet their basic needs by setting such a minimum wage. ••• Indonesian ••• UU No. 11/2020 tentang Cipta Kerja merupakan perubahan dari UU No. 13/2003 tentang Ketenagakerjaan. Undang-undang tersebut disahkan pada tahun 2020. Dalam pengesahannya, banyak tenaga kerja yang tidak setuju dengan beberapa pasal yang terdapat dalam undang-undang tersebut, salah satunya adalah Pasal 89 Ayat (1) yang membahas tentang upah minimum. Tenaga kerja tidak setuju dengan pasal ini karena adanya perubahan upah minimum provinsi menjadi upah minimum provinsi dan upah minimum kabupaten/kota. Perubahan upah minimum dikhawatirkan akan menimbulkan ketidakadilan antara tenaga kerja dan pengusaha. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis konsep upah minimum tenaga kerja yang bekerja dalam UU No. 11/2020 yang berpedoman pada fiqh muamalah. Metode yang digunakan dalam penelitian ini adalah jenis studi yuridis normatif atau kepustakaan dengan mengambil pendekatan hukum dan konseptual dalam fiqh muamalah dengan menelaah dokumen melalui beberapa data untuk menganalisis konsep upah minimum tenaga kerja dalam UU No. 11/2020. Hasilnya adalah, dalam penentuan besaran upah minimum berdasarkan kesejahteraan tenaga kerja, UU No 11/2020 tidak sesuai dengan apa yang dijelaskan dalam fiqh muamalah. Peneliti menyarankan agar data yang digunakan dalam penentuan upah minimum hanya berdasarkan pertumbuhan ekonomi dan inflasi harus bersyarat. Karena pada dasarnya tidak semua tenaga kerja dapat memenuhi kebutuhan dasarnya dengan menetapkan upah minimum tersebut.